Does an institutional factor influence corporate environmental strategy?: Looking through the Guanxi lens. Issue 1 (6th March 2017) - Cao, Xuanwei; Quazi, Ali
Abstract : Purpose: This paper aims to illustrate how institutional factors, such as Guanxi (connectedness) mechanism in a transition economy, could impact managerial cognition and their temporal orientation at individual level as well as induced change on corporate environmental strategy (CES). More specifically, this paper explores the micro foundation of corporate strategy change in an attempt to examine how corporate strategic choice and actions evolve with managerial cognition of "Guanxi" with various temporal orientations. Design/methodology/approach: The paper reviews the extant literature focusing on Guanxi and CES with special attention to the temporal orientation in strategy formulation. A conceptual framework is proposed to analyze the underlying mechanism of Guanxi in mediating and shaping CES. A multi-case study with four companies operating in two industry sectors were investigated considering their relative long foothold as well as their different postures and dynamic change of corporate environment strategy in the past decades. Findings: The findings support recent critiques on the likely shift in strategic choice of firms from the traditional Guanxi-based to a rule-based format. The interactions between entrepreneurial cognition and strategic activities toward environmental issues were still influenced by deep relational embeddedness. The findings proved that managerial Guanxi cognition impacts managers' temporal orientation and their strategic choice on CES. Foreign-invested enterprises in the process of localization face the potential risk of emerging backdrop of their CES, i.e. from more active strategy to more reactive strategic posture, whereas local private-owned enterprises show a transformation from reactor to follower and even pioneer in the wave of those entrepreneurs' changing cognition on the role of Guanxi in their businesses. Research limitations/implications: One main limitation of the study is the lacking of quantitative measurement of corporate environment performance. Although the paper used multiple cases to explore the dynamics of Guanxi on impacting CES, only with further development of effective scale measurement to test corporate environment performance can increase the explaining power of the proposed theoretical model in this study. It is important to note that with data of longitudinal measurement of corporate environment performance, it would be more convincing to show the outcome of the temporal lens of Guanxi on CES. However, the lacking availability of qualified disclosed data on indicating corporate environment performance constrains another limitation for the study. Considering the complexity of corporate environment strategy, the focus cases in the paper might still lack powerful and convincing illustration to prove the impact of Guanxi on CES despite the enriched contextual data and description. It is necessary to conduct deeper analysis to exclude the impact of other possible factors on CES to highlight the direct impact of Guanxi on CES. Practical implications: The results of the in-depth analysis and interpretation of the exploration of the cases suggest that Guanxi still seems to dominate managerial thinking process as the norm is deeply rooted in their mind sets. However, Guanxi is no longer considered as a mere reactive cultural norm rather a positive mechanism through which Chinese firms can achieve their sustainable environmental strategic goals as well as economies prosperity in the rapidly competitive business landscape in modern China. Originality/value: Previous research on CES largely neglected the context factors. This paper presents a conceptual model to deepen our understanding of the contextual factor of Guanxi with a temporal perspective and its consequent influence on CES. This helps policy makers as well as strategic management researchers and academics to reconsider the mechanism of adaptation and selection in shaping CES in the event of large scale institutional change.